Rapid deglacial injection of nutrients into the tropical Atlantic via Antarctic Intermediate Water - Poggemann, David Willem; Bahr, André (Earth and planetary science letters, 2017)
As part of the return flow of the Atlantic overturning circulation, Antarctic Intermediate Water (AAIW) redistributes heat, salt, CO2 and nutrients from the Southern Ocean to the tropical Atlantic and thus plays a key role in ocean-atmosphere exchange. It feeds (sub)tropical upwelling linking high and low latitude ocean biogeochemistry but the dynamics of AAIW during the last deglaciation remain poorly constrained. We present new multi-decadal benthic foraminiferal Cd/Ca and stable carbon isotope (δ13C) records from tropical W-Atlantic sediment cores indicating abrupt deglacial nutrient enrichment of AAIW as a consequence of enhanced deglacial Southern Ocean upwelling intensity. This is the first clear evidence from the intermediate depth tropical W-Atlantic that the deglacial reconnection of shallow and deep Atlantic overturning cells effectively altered the AAIW nutrient budget and its geochemical signature. The rapid nutrient injection via AAIW likely fed temporary low latitude productivity, thereby dampening the deglacial rise of atmospheric CO2.